The Impacts of Trichomonas vaginalis on the Quality of Life in Women - Brown, Samuel Tamunoiyowuna Cockeye; Mohammed, Usman Ikrimah; Onyemaechi, Eze Emmanuel; Wama, Yusuf Precious (Darul Yasin Al Sys, 2025)
Trichomoniasis is a significant global health concern, particularly affecting women of reproductive age. In many public health settings, diagnosis is commonly based solely on clinical signs and symptoms. However, this approach can lead to misdiagnosis, as trichomoniasis shares similar clinical presentations with other vaginal infections. Caused by the protozoan Trichomonas vaginalis, trichomoniasis is one of the most prevalent non-viral sexually transmitted infections (STIs), often linked to reproductive tract infections, infertility, cervical cancer, premature births, and low birth weight in newborns. According to the World Health Organization, approximately 276.4 million cases were reported in 2008, with nearly 90% occurring in resource-limited settings. The global prevalence among women is estimated at 8.1%, making it more common than Chlamydia trachomatis, Neisseria gonorrhoeae, and syphilis combined. Various studies have identified key risk factors associated with T. vaginalis infection, particularly among adolescent girls and women attending STI clinics. These include unprotected sexual intercourse, multiple sexual partners, a longer history of sexual activity, previous STIs, and higher prevalence among Black populations. Beyond its physical health implications, trichomoniasis significantly impacts women’s quality of life, affecting sexual function, reproductive outcomes, mental health, and social well-being. The stigma surrounding STIs, coupled with the often asymptomatic nature of trichomoniasis, contributes to delayed diagnosis, untreated infections, and continued community transmission. Effective prevention and control require comprehensive strategies including safe sex practices, regular screening, early diagnosis, partner notification, and timely treatment. Addressing the broader social and psychological dimensions of the disease is essential for improving health outcomes and reducing the burden of trichomoniasis on women’s health globally.